Predicting malignancy in adnexal masses by the international ovarian tumor analysis-simple rules - Vrushti Solanki; Pratibha Singh; Charu Sharma; Navdeep Ghuman; Binit Sureka; Shashank Shekhar; Meenakshi Gothwal; Garima Yadav (Wolters Kluwer Medknow Publications, 2020)
Background: Accurate prediction of adnexal tumors preoperatively is critical for optimal management of ovarian cancers. The International Ovarian Tumor Analysis Algorithms (IOTA) is a newer tool to characterize adnexal masses as benign or malignant. Objective: This study is aimed to predict malignancy in adnexal masses and differentiates benign from malignant, applying the sonography features of simple rules given by IOTA. Methodology: A prospective study was carried out at AIIMS Jodhpur for 1½ years. Women presenting with adnexal masses planned for surgery were recruited. Ultrasonography-transabdominal combined with transvaginal was done, and pelvic masses were characterized using IOTA simple rules. Patients underwent their planned surgery. Histopathology is considered the gold standard and was compared with the IOTA simple rules. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: One hundred and seventy-four women were included in the study, of which the majority (82.75%) were benign, the rest being frankly malignant or borderline cancer. The sensitivity of IOTA is 96.6%, specificity of 92.3%, PPV of 72.5%, NPV of 99.2%, where indeterminate cases were considered malignant. Conclusion: IOTA simple rule is an effective tool for identifying malignant adnexal masses. It also suggests that IOTA-simple rules can be used as a diagnostic criterion for differentiating adnexal masses into benign and malignant on an out-patient department basis.